Analisis Manajemen Keuangan Sekolah Dalam Mendukung Kualitas Pembelajaran Di Sd Labschool Unesa 1 - Shakira Maeizy Hamdi Bajeber; Nisaul Fauziah; Lailatul Eka Fitriani; Nur Ainiyah; Sania Tri Wahyuni; Ima Widiyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
School financial management plays a strategic role in supporting the quality of learning. This study aims to analyze the processes of planning, implementation, monitoring, and the impact of financial management on the quality of learning at SD Labschool Unesa 1. The study employs a descriptive qualitative approach, utilizing data collection techniques such as in-depth interviews, observations, and document analysis. Research informants included the school principal, the school treasurer, and the BOS treasurer. The results indicate that SD Labschool Unesa 1 manages two parallel funding streams: internal funds from the UNESA Foundation and external government funds (BOS). The budget plan (RKAS) is developed through a participatory process and is based on data from the Education Report Card. Budget implementation employs a strict proposal mechanism with documented accountability, while oversight is conducted in layers and reporting utilizes the ARKAS application. This transparent and accountable financial management has a positive impact on the provision of facilities and infrastructure as well as the continuous implementation of learning programs. The main challenges faced include the lengthy implementation of development programs through the foundation and the dynamics of policy changes midway through the fiscal year.